EFEKTIVITAS PEMBEBASAN PPN ATAS KEBUTUHAN POKOK DALAM PERLINDUNGAN KONSUMEN MENENGAH BAWAH: STUDI LITERATUR - Niken; Pasha Anggrainy; Yuniati (LPPM STIE YKPN Yogyakarta, 2026)
This research was conducted to examine the impact of the Value Added Tax (VAT) policy, specifically the VAT exemption, on the prices of basic necessities. This study highlights its implications for public purchasing power and consumer protection, particularly for the most vulnerable lower-middle-income groups. The research method employed was a literature review, reviewing data obtained from various scientific sources, such as books, academic journals, and relevant laws and regulations. Based on the research results, it is known that VAT exemption can affect the price of goods, although it is not always followed by an immediate price reduction. This condition is influenced by various other factors, such as the inflation rate, distribution system, and market conditions. Increased prices of goods have the potential to reduce public purchasing power and lead to decreased consumption. Furthermore, consumer protection is a crucial aspect of fiscal policy, given that consumers are generally at a lower level than businesses. In conclusion, the VAT exemption policy needs to be supported by supporting policies such as subsidies or social assistance to maintain public purchasing power and increase consumer protection, especially for vulnerable groups.